Geochemical and Sr–Nd isotopic constraints on the petrogenesis of the Goesan monzodiorite pluton in the central Okcheon belt, Korea. (January 2016) - Cheong, Chang‐Sik; Jo, Hui Je; Jeong, Youn‐Joong; Park, Chan‐Soo; Cho, Moonsup
Abstract: The Permian–Triassic high pressure metamorphism and potassic magmatism in central Korea attest to the extension of the Dabie‐Sulu collision belt in central‐eastern China towards the Korean Peninsula and possibly the Japanese Islands. We present major and trace element and Sr–Nd isotope data for a ca. 230 Ma monzodiorite pluton emplaced in the Goesan area, central Okcheon belt, Korea. This pluton shows geochemical features comparable with those of the coeval monzonite–syenite–gabbro–mangerite suite documented recently in the Gyeonggi massif. The metaluminous and alkali–calcic signatures of the Goesan intrusives correspond to the Caledonian‐type post‐orogenic granitoids. The K2 O/Na2 O ratios of all analyzed samples are greater than 1, and are not correlative with their SiO2 contents. The enrichment of both large‐ion‐lithophile elements and highly compatible elements in the Goesan pluton is probably indicative of metasomatized mantle origin. The elemental fractionation in the source region must have occurred in the distant past, possibly the Paleoproterozoic, to generate significantly negative εNd (t) values (< –16). Chondrite‐normalized rare earth element patterns as well as Rb/Sr and Ba/Rb ranges suggest that the source consists of amphibole‐bearing rocks. Progressive decreases in negative Eu anomaly and Ba, Sr, Ni, Cr and V contents with increasing SiO2 contents reflect an important role of plagioclase, biotite and hornblende for the fractionation process. Zr is undersaturated in the potassic, metaluminous melt. The initial Sr–Nd isotopic compositions of the samples are correlated with their SiO2 contents, substantiating a role of crustal assimilation during the magmatic differentiation. The Sr–Nd elemental and isotopic modeling suggests that the Goesan pluton was initially slightly heterogeneous in its isotopic composition, and underwent concurrent assimilation and fractional crystallization. The occurrence of the Goesan pluton provides further evidence corroborating the amalgamation of allochthonous terranes within the Okcheon belt during the Permian–Triassic collisional orogeny. Abstract : We report major and trace element and Sr‐Nd isotope data for a Late Triassic monzodiorite pluton emplaced in the Goesan area, central Okcheon belt, Korea. The metaluminous and alkali‐calcic signatures of the Goesan intrusives correspond to the Caledonian‐type post‐orogenic granitoids. The Sr‐Nd elemental and isotopic modeling suggests that the Goesan pluton underwent concurrent assimilation and fractional crystallization.